Dutch soccer secrets : playing and coaching philosophy--coaching, tactics, technique - Hyballa, Peter , 1975-; Poel, Hans-Dieter te (Meyer & Meyer Sport, 2012)
Learn how a nation of about 16 million inhabitants can regularly produce world-class players or coaches like Johan Cruyff, Arjen Robben or Dick Advocaat and Louis van Gaal